PENGEMBANGAN KARAKTER ANAK USIA DINI MELALUI PEMBELAJARAN MODEL PARENTING - Rokyal Harjanty; Sry Anita Rachman; Farlina Hardianti (LPPM Institut Pendidikan Nusantara Global, 2020)
The objectives of this study were (i) to describe the level of character development needs of early childhood through parenting model learning in RA Barokatus Saulatiyah. (ii) Knowing the early childhood character development prototype through parenting model learning in RA Barokatus Saulatiyah. (iii) Knowing the analysis of the level of validity and practicality of early childhood character development through parenting model learning in RA Barokatus Saulatiyah. This type of research is a type of research and development (research and development). The research subjects were teachers and parents. The data analysis technique used is to analyze the data in a descriptive and practical way. The results showed that (i) The level of need for Early Childhood Character Development through Parenting Model Learning in RA Barokatus Saulatiyah can be illustrated that there is still a lack of understanding from educators, especially teachers and parents about the importance of shaping early childhood character, this shows that teachers in the group are still found. B complained that 2 parents (out of 15 children in group B) often asked for homework in the form of reading, writing, arithmetic (calistung). Kindergarten teachers who already understand the stages of child development end up in a dilemma because theoretically it is known that learning to read for early childhood cannot be forced; (ii) An overview of the design form of Early Childhood Character Development through Parenting Model Learning consists of two components, namely the model philosophy component and the model implementation component. The components of the model philosophy include rationality, goals, teacher roles and system support. Meanwhile, the operational components of the model are described in detail in all types of activities with different themes. All activities are packed with the aim of developing early childhood character; (iii) The level of content validity and practicality of Early Childhood Character Development through Parenting Model Learning at RA Barokatus Saulatiyah, indicates that the validator's assessment of all the tools that have been presented can be declared valid for use and development of Early Childhood Character Development through Parenting Model Learning meets practical aspects so that it is suitable for use.